Clinical and polysomnographic features of children evaluated with polysomnography in pediatric sleep laboratory - (:unkn) unknown (AVES, 2017)
Aim: Sleep disordered breathing is a common problem in childhood that encompasses a spectrum of disorders extending from primary snoring to obstructive sleep apnea. This study aims to investigate the results of children undergoing evaluation with polysomnography in the sleep laboratory of a tertiary care hospital. Material and Methods: Demographic and clinical features as well as sleep associated symptoms, scores of pediatric sleep questionnaire and Pittsburgh sleep quality index and polysomnography results are retrospectively evaluated. Results: Totally 131 patients were evaluated, of which 47.3% (n=62) were females and 52.7% (n=69) were males. Mean age was 101.85 +/- 59.15 months at the time of the study. Fifty percent (n=59) of patients complained of snoring and 43.7% (n=52) of patients complained of apnea during sleep. Mean obstructive hypopnea-apnea index was 5.12 +/- 11.72. Mean obstructive hypopnea-apnea index of snorers (6.93 +/- 13.53) was significantly higher than the mean obstructive hypopnea-apnea index of nonsnorers (2.32 +/- 5.43) (p=0.011). Mean obstructive hypopnea-apnea index of patients experiencing apnea during sleep (7.52 +/- 14.25) was significantly higher than the mean obstructive hypopnea-apnea index of the children who do not experience apnea (2.61 +/- 5.84) (p=0.008). No significant correlation was observed between obstructive hypopnea-apnea index and scores of pediatric sleep questionnaire and Pittsburgh sleep quality index. The prevalence of obstructive sleep apnea was 33.6% (n=44). Forty nine patients (39.8%) were treated after polysomnography. Frequently suggested treatment options were noninvasive mechanical ventilation (n=23, 46.9%), intranasal steroid (n=15, 30.6%), montelukast (n=11, 22.4%) and adenotonsillectomy (n=9, 18.4%). Conclusions: Polysomnography is the gold standard in the diagnosis of sleep disordered breathing in children. Pediatricians should be able to recognize early signs and symptoms of sleep disordered breathing and refer the patients in risk to centers where evaluation with polysomnography is available.
Keywords: Child; obstructive sleep apnea; polysomnography; sleep disordered breathing; POSITIVE AIRWAY PRESSURE; APNEA SYNDROME; LONGITUDINAL IMPACT; CHILDHOOD; ADOLESCENTS; MANAGEMENT; OVERWEIGHT; DIAGNOSIS; OBESITY; QUESTIONNAIRE